2012
DOI: 10.1007/s12010-012-9628-5
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Selenium and Light Wavelengths on Liquid Culture of Cordyceps militaris Link

Abstract: To investigate the effects of selenium and light wavelengths on the growth of liquid-cultured Cordyceps militaris and the main active components' accumulation, culture conditions as selenium selenite concentrations and light of different wavelengths were studied. The results are: adenosine accumulation proved to be significantly selenium dependent (R(2) = 0.9403) and cordycepin contents were determined to be not significantly selenium dependent (R(2) = 0.3845) but significantly enhanced by selenium except for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
23
2
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 27 publications
3
23
2
1
Order By: Relevance
“…Curiously, we found that the presence of sodium selenite did not induce the production of adenosine and cordycepin, which is in disagreement with the promoting activity of selenium on nucleosides produced by C . militaris [15]. Selenium complexes can promote the activity of several enzymes involved in cordycepin synthesis [60].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Curiously, we found that the presence of sodium selenite did not induce the production of adenosine and cordycepin, which is in disagreement with the promoting activity of selenium on nucleosides produced by C . militaris [15]. Selenium complexes can promote the activity of several enzymes involved in cordycepin synthesis [60].…”
Section: Discussionmentioning
confidence: 99%
“…These may be extracted from fruiting bodies or mycelia and are currently studied as therapeutic agents [78, 10, 1213]. Nucleosides can be differentially induced by intrinsic or environmental factors, such as the developmental stage of the fungus, light exposure and wavelength, the composition of the culture media, among other factors [78], [1215]. Traditionally, the nucleosides cordycepin (3’-deoxyadenosine), adenosine, inosine, guanosine, and uridine have been used as markers to assess the quality of natural and cultured species of Cordyceps [4, 1617].…”
Section: Introductionmentioning
confidence: 99%
“…Except for the traditional cultivation factors such as culture medium components and temperature, other new physical factors as selenium and lightening of special wavelengths [17] were reported to significantly enhance activity of fungus species as Cordyceps militaris. So new cultivation methods to promote hydrolysis activity of P. dioscin spawn deserves further research.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is known that metabolite production is affected by environmental factors such as light exposure and culture medium components. Many previous studies have investigated the effects of environmental changes on the production of secondary metabolites in Cordyceps species [9][12]. In addition, there have been many studies of antioxidants from other Cordyceps species, including C. militaris and C. sinensis [13], [14].…”
Section: Introductionmentioning
confidence: 99%